History and Value of Batalam Tradition in Koto Baru Payakumbuh (1942-1990) - Putri, Salsabila Dwi; Aisyah, Siti; Yulniza, Yulniza (Journal of Philology and Historical Review, 2024)
Batalam is one of the traditions that is still carried out by the people of Koto Baru Village, Payakumbuh, West Sumatra. Over time, talam continues to change, especially in terms of the use of materials. The purpose of this research is to analyze the changes that have occurred in the batalam tradition in Koto Baru, and to analyze the meaning of the batalam tradition for the local community. This research uses historical research methods. The steps in the historical research method used in this research are heuristics, source criticism, synthesis and writing or historiography.  The results of this study indicate that since before 1942, there has been a significant change from the batalam tradition, previously the community used katidiang tunggak, while after 1942, it began to switch to talam or dulang. Until the 1990s, there was no longer a change in shape, but only a change in the material of the talam, from previously made of brass to aluminum, besides that there was also a change in the material of the cup which was originally made of glass to plastic. Despite the change in materials, the value contained in this tradition is still the same, which is related to symbols of togetherness, respect, and closeness.